The The Legal Liability of Insurance Companies on Unit-Linked Insurance Plan's Mis-Selling Practices Done by Insurance Agents: an Approach to Law Number 4 of 2023 Concerning the Development and Strengthening of the Financial Sector (PPSK Law) - Levina Kezia; Christine Kansil (Dinasti Research, 2024)
The purpose of this study aims to analyze the legal liability of an insurance company when an Unit-linked Insurance Plan (ULIP) products is mis-sold by an insurance agent. Using the normative judicial method, this study also examines the main factors of mis-selling practices and the legal responsibilities that both insurance companies and their agents have to carry based on Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (PPSK Law). The results revealed that many insurance agents have a poor knowledge of how ULIP and its investment works. High-pressure sales techniques is also often used by insurance agents to manipulatively persuade policyholders into buying ULIP, which then consequently leads into mis-selling. In accordance to the current PPSK Law, insurance company as the principal of the legally binding agency agreement is liable for the negligent actions commited by their agents, including when they mis-sell an ULIP product, however insurance agents can also be held liable for the negligent actions that are commited outside the scope of their authorities.